Globalization And Agrarian Civilization - I., Glazko V.; Yu., Kosovski G. (Advances in Social Sciences Research Journal, 2018)
The paper presents a review of the events preceding the formation of an interdisciplinary research area, globalistics, and discusses some historical factors in its establishment. The globalistics is reviewed as a scientific discipline studying the history of agrarian civilization and the results of its interaction with the natural ecosystems. Impacts of some doctrines in the formation of a new sphere of scientific knowledge, globalistics, are reviewed. These include the doctrines of: V.I. Vernadski on biosphere, N.I. Vavilov on centers of domestication, N.D. Kondrat’yev on cycles of the global economics.